Conditional cash transfers in Guatemala - LOPEZ LOPEZ, Jazmin Isabel (KDI School, 2015)
Conditional Cash Transfer (CCT) has been a social program widely known and replicated all around the world, having as main purpose of reducing of poverty through the investment on education, health and nutrition of children in low income families. Using coresponsibilities, the benefited families compromise to use the cash transferred by the government on their kids. With this social policy, the human capital is formed and further developed. In order to do so, having a clear update framework is necessary to keep improving the performance of the CCT program and specially to obtain the positive outcomes that are expected to be achieved. In the regard, this study analyze the current situation of the CCT program in Guatemala, conducting a simulation on reform and adjustment on the amount of CCT. Moreover, this study determines the updated parameters of the eligibility criteria to be applied to the aforementioned program. Finally, this study examines the Mexican CCT program by conducting a comparative analysis with the Guatemalan program, in order to design a policy implication of how to reform and keep updating the program in Guatemala.
Thesis(Master) --KDI School:Master of Development Policy,2015